Levels of Some Heavy Elements in Corn and Some Product - Nada Naji Tawfeeq; Ibtehaj Mustafa Hakeem (International Journal of Medical Toxicology and Legal Medicine, 2025)
Ten heavy elements (Cd, Pb, Hg, Cr, Ni, Al, Mn, Co, Cu, Mg) in raw corn from four different Iraqi governorates were collected, boiled, oil extraction and corn bread made were examined by atomic absorption spectrophotometer (AAS) after wet digestion. The results showed that the levels of elements (Cd, Pb, Hg, Cr, Ni, Al, Mn, Co, Cu, Mg) were at average 0.047, 0.313, 0,0016, 1.317, 67.401, 9.825, 66.975, 13.763, 10.078 and 502.75 mg/kg in raw corn, 0.154, 0.165, 0.0585, 1.143, 1.154, 15.278, 44.603, 6.395, 4.395 and 916 mg/kg in boiled corn,0.026, 4.025, 0.0038, 2.2, 0.525, 0.683, 0.855, 1.888 , 2.848 and 9.903 mg/kg in the extracted oil and 0.49, 7.402, 0.0045, 2.4, 1.748, 21.613, 6.597, 0.838, 1575 and 852.25 mg/kg in corn bread, respectively. The results also showed a decrease in the levels of Pb, Cr, Ni, Mn, Co and Cu in boiled corn, and Pb, Ni, Al, Mn, Co, Cu and Mg in the extracted oil and Ni, Mn, and Co in corn bread, while, increase the elements Cd, Hg, Al and Mg in boiled corn and Cd, Hg and Cr the extracted oil and Cd, Pb, Hg, Cr, Al, Cu and Mg in corn bread. The results showed that the levels of Cd, Pb, Cr, Ni, Co and Cu exceeded the permissible limits according to the Codex Alimentarius Commission, which indicates contamination of corn grown in Iraq, which is reflected in the health of humans or animals that feed on it.